Application of the Indirect Immunoperoxidase Stain Technique to the Flagella of Azospirillum brasilense - Hall, Patrick G. (1984)
An indirect immunoperoxidase stain was used to demonstrate by electron microscopy that an antigenic difference exists between the polar flagellum and the lateral flagella of Azospirillum brasilense ATCC 29145.